Chain-mediated effect of physical activity between Chinese language-based L2 motivational self-system and intended effort - Zixia Bu; Yu Liu; Yi Ba; Shan Jiang; Huijuan Liu; Jiyuan Li; Fuqiang Dong; Haohan Yu; Xindi Zhao (Scientific Reports)
Abstract The L2 Motivational Self System (L2MSS) determines an individual’s motivation in second language learning and influences the learning experience and intended effort. Although physical activity (PA) has been shown to enhance academic efficacy, the role of PA in whether it promotes second language learning efficacy has not been elucidated. Therefore, the present study examined PA as a mediator and explored its ameliorative effects in L2MSS. A total of 981 international students from different countries were selected from 8 universities in Beijing as research subjects and were surveyed by International Physical Activity Questionnaire (IPAQ), L2MSS, Learning Experience Scale, and Intended Effort Scale. Differences, correlations, and mediated model were analyzed by ANOVA, Pearson, and structural equation modeling (SEM). The proportions of PA in this study were comparable to those observed in previous studies, with the lowest prevalence of individuals exhibiting high levels of PA, followed by those with medium levels, and the highest prevalence of individuals with low levels. With the exception of ideal L2 self, PA had a significant enhancing effect on L2MSS, learning experience, and intended effort (F = 2.36, η²=0.05, ; F = 3.16, η²=0.04, ; F = 2.33, η²=0.05; P < 0.05), and was incrementally associated with ought-to l2 self, endeavor degree, and time spent (F = 4.23, η²=0.05, ; F = 7.21, η²=0.04, ; F = 5.93, η²=0.03; P < 0.01). In terms of correlations, there were general and significant positive correlations between PA and the rest of the indicators (r > 0.3, P < 0.05), except for learning desire and ought-to L2 self (r = 0.293). According to the SEM test, in addition to the direct effect of L2MSS on intended effort, the following paths existed: (1) ILS→PA→IE (effect=-0.265, ratio = 31.28%, 95%CI=[0.124, 0.527]), (2) OLS→PA→IE (effect = 0.179, ratio = 17.94%, 95%CI=[0.074, 0.256]), (3) ILS→PA→LE→IE (effect = 0.116, ratio = 10.69%, 95%CI=[0.042, 0.248]), (4) OLS→PA→LE→IE (effect = 0.108, ratio = 4.15%, 95%CI=[0.039, 0.126]). total indirect effect为0.304 (ratio = 59.61%, 95%CI=[0.069, 0.289]). (1) PA had an ameliorative effect on L2MSS, learning experience, and intended effort, and increasing PA level increased the significance of this effect. (2) PA level positively predicts L2MSS, learning experience, and intended effort. (3) PA is an important mediator in the process of L2MSS that influences the learning experience and intended effort, so MPA at least 3 days a week can increase the efficiency of second language learning. This study will provide a referable predictive model and a richer theoretical foundation for Chinese language learning and dissemination.